PENGARUH KARAKTERISTIK ORGANISASI TERHADAP EFEKTIVITAS ORGANISASI PADA PT. ADIRA PEKANBARU - Ristiliana, Wenny Desty Febrian, (Universitas Batanghari Jambi, 2018)
AbstractThis study aims to analyze the influence of organizational characteristics on organizational effectiveness at PT. ADIRA in Pekanbaru. The type of this research is quantitative research. Population in this research is all employees of PT. ADIRA Finance in Pekanbaru totaling 416 people, who then withdrawn the sample using slovin formula to as many as 80 employees. The technique of sampling using proportional random sampling tekik. Technique of data analysis by using linear regression analysis. The results showed that there is significant influence of organizational characteristics on organizational effectiveness either simultaneously or partially. This result is seen from the value of significance obtained that is 0.011 smaller than the value of probability 0.05 or the value is said 0.011 <0.05 so that the conclusion variables X and Y have a significant effect.Keyword: Organizational Characteristics, Organizational Effectiveness